Coherence in Discourse. A Study in Dynamic Text Theory - Fritz, Gerd; Justus Liebig University Giessen (My University, 2022)
Texts and (contributions to) conversations mostly show a kind of orderliness and serial connectedness that makes them comprehensible and useful. Accordingly, a theory of coherence has to account for the resources and strategies used by speakers/writers in achieving this orderliness and connectedness and by hearers/ readers in understanding it. The present book approaches this task from an action-theoretic perspective, focusing in particular on the dynamics of act sequencing and modelling the step-by-step solution of communicative tasks in the course of text production and dialogical communication. Individual chapters (and sections) deal with the following topics, among others: the basic building blocks of discourse, resources of coherence and their use, speech act sequencing, coherence and coreference, coherence and topic management, coherence and text types, coherence and understanding, coherence and intertextuality, types of connectivity in text/image configurations, coherence and Artificial Intelligence, topics as resource and an achievement in dialogue.
Keywords: Textkohärenz; Dialogkohärenz; Sprechaktsequenzen; Kontextveränderung; Themenentwicklung; Textdynamik; Dialogdynamik; ddc:400